Evaluation of Pathogen Reduction and Compost Quality in Takakura Method Composting of Organic Waste and Disposable Diapers - Fazrian, Sitti Adiyaksa; Widyastuti, Sri; Al Kholif, Muhammad; Pungut, Pungut (Brawijaya University, 2024)
ABSTRACTThe use of disposable diapers contributes significantly to environmental issues. One approach to address this issue is to compost. The Takakura method offers a potential solution, although feces in diapers raises concerns about pathogen contamination. This study aimed to evaluate the safety and quality of compost produced from organic waste and disposable diapers using the Takakura method, focusing on fecal coli levels. Organic waste is a mixture of vegetable and fish waste in different proportions. The two treatments tested were 75% organic waste (vegetable/fish) + 25% diapers and 25% organic waste + 75% diapers, observed on days 10 and 20. On day 20, the 75% fish waste + 25% diaper mixture produced the lowest fecal colony level (33 MPN/g), meeting the Indonesian National Standard (SNI) No. 19-7030-2004. The decrease in fecal coli levels was due to microbial interactions, including lactic acid bacteria and Bacillus from fish waste, which have antimicrobial properties. This study shows that composting disposable diapers with the Takakura method and organic waste can produce compost that meets the standard, especially with 75% organic waste composition. However, due to potential pathogen risks, it is more suitable for non-food crops. Keywords: composting, disposable diapers, MPN fecal coli, organic waste, Takakura